A study on activation mechanism in perspective of lignin structures and applicability of lignin-derived activated carbons for pollutant absorbent and supercapacitor electrode. (March 2022) - Hwang, Hyewon; Ajaz, Ahmed Muhammad; Choi, Joon Weon
Abstract: In this study activated carbons were produced from the biorefinery waste lignin (Asian lignin (AL) USA & Inbicon lignin (IL) Denmark) to evaluate their potential in waste water treatment and as energy storage devices. These products were studied for their surface characteristics as a function of reaction temperature, time, and catalyst loading accordingly. Under the conditions with a temperature lower than 750 °C and within a reaction time of 1 h, the catalytic reaction of alkali-carbon bonding occurred from the external surface, and a turbostratic disorder structure with a large aromatic ring system was formed. More severe reaction conditions accelerated the volatile release of de-alkylated aromatics such as benzene and naphthalene, along with structure and surface collapse. The maximum BET surface area of 2782 m 2 /g was obtained at 750 °C, 2 h and catalyst ratio of 4. Lignin-derived activated carbon was more efficient for the removal of organic pollutants (<50% adsorption capacity) rather than heavy metals (adsorption capacity >90%) due to interaction of π-π bonding. Furthermore, the activated carbon has a potential to be used as a supercapacitor electrode with high specific capacitance (214.0 F/g AL lignin) and an excellent cyclic stability (95% of their initial capacity). The results of this study demonstrate that lignin is an attractive precursor to produce activated carbons with diverse applications both as biosorbent and as a carbon electrode material even so with acceptable performance. Graphical abstract: Image 1 Highlights: Lignins were subjected to catalytic activation under various temperature and reaction time. Lignin derived activated carbon showed promising surface area and turbostratic disorder structures. Activated carbons show excellent adsorption capacity for organic pollutants Phenol, BPA and 2, 3-D. Electrode fabricated with activated carbons has good cycle stability and specific capacitance.